"2-step MCI-AD": a simple scoring system to predict rapid conversion from mild cognitive impairment to Alzheimer dementia. (May 2021) - Muscari, Antonio; Clavarino, Fabio; Allegri, Vincenzo; Farolfi, Andrea; Macchiarulo, Maria; Maestri, Lorenzo; Sessagesimi, Elisa; Spinardi, Luca; Lunardelli, Maria Lia
Highlights: Not all patients with Mild Cognitive Impairment convert to Alzheimer dementia Simple cost-effective methods to assess the risk of conversion are not available yet Two neuropsychological tests plus CT scan may identify patients at high or low risk Only patients with intermediate risk might subsequently undergo FDG-PET assessment This scoring-system may prove useful in every-day practice in geriatric clinics Abstract: Background: Several techniques are available to identify, among patients with mild cognitive impairment (MCI), those at risk of conversion to Alzheimer dementia (CAD). However, simple cost-effective methods to assess the risk are not available yet. Methods: This retrospective study included 143 MCI outpatients (76.6±5.2 years, 46.8% women). Baseline variables were common neuropsychological tests (including Mini Mental State Examination-MMSE and Montreal Cognitive Assessment-MoCA), brain CT and 18F-fluorodeoxyglucose (FDG)-PET. Outcome variable was CAD after 1 year. Results: At follow-up, 31 (21.7%) patients had CAD. In multivariable analysis (OR, 95% CI), female sex (4.7, 1.6-14.0), MoCA-executive component <3 (6.3, 2.1-19.2), left medial temporal atrophy (MTA) ≥3 (5.4, 1.9-15.7) and FDG-PET suggesting CAD (5.4, 1.9-15.7) were associated with CAD (area under ROC curve 0.873). Without FDG-PET, MMSE score <28 remained associated with CAD (6.0, 2.2-16.9). As first step (before FDG-PET execution), we counted 1 point for MMSE <28, executive MoCA <3 and left MTA ≥3. With 2-3 points CAD probability was high (75%) and with 0 points it was low (6.5%). Thus, FDG-PET (second step) might be performed only in patients with 1 point (probability 19.7%, 42.7% of patients). Among them, 35% had a positive FDG-PET, suggesting high risk. Overall, 28.0% of patients were considered at high risk (specificity 83.9%, sensitivity 71.0%, accuracy 81.1%). Conclusion: With a 2-step procedure, less than half of MCI patients might undergo FDG-PET and nearly a quarter of our patients was found to be at high CAD risk, including almost three quarters of future CADs. Graphical abstract: Image, graphical abstract